2022
DOI: 10.1007/s10643-021-01295-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perspectives of Preschool Teachers on Implementing Structured Motor Programs in Inclusive Classrooms

Abstract: Children with disabilities (CWD) tend to participate in fewer physical activities than typically developing children. During motor play, CWD often depend on teachers to provide direct instruction and frequent opportunities to practice motor skills, to interact with their peers, and learn new skills. To promote participation in physical activities for CWD, it is necessary to understand (a) teachers’ perceptions about the importance of structured motor programs and (b) teachers’ thoughts and concerns about imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…A few participants in the current study were frustrated that they did not have access to resources for motor play from their schools (Cheung, Ostrosky et al, 2022) . Teachers may consider how families can adapt common household materials (i.e., socks, dish towels, buckets) for motor activities and embed motor play into naturally occurring daily routines, ideas that are described by Cheung, Ostrosky and colleagues (2022).…”
Section: Logistical Issuesmentioning
confidence: 87%
See 2 more Smart Citations
“…A few participants in the current study were frustrated that they did not have access to resources for motor play from their schools (Cheung, Ostrosky et al, 2022) . Teachers may consider how families can adapt common household materials (i.e., socks, dish towels, buckets) for motor activities and embed motor play into naturally occurring daily routines, ideas that are described by Cheung, Ostrosky and colleagues (2022).…”
Section: Logistical Issuesmentioning
confidence: 87%
“…In the current study, almost all teachers reported that they attempted to embed motor play into their virtual curriculum, but they were challenged to implement some activities effectively. In fact, even during in-person learning, teachers reported that they lacked sufficient knowledge to implement motor play in inclusive preschool settings and that they wanted more training in this area (Cheung, Ostrosky et al, 2022;Gehris et al, 2015;Hughes et al, 2010). Not surprisingly, it is even more challenging to embed motor play virtually, and it can be especially difficult to engage children with disabilities and create active learning opportunities within virtual environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outdoors, it is speculated that the verbal interactions may have occurred when the children were engaging in risky play, and the educator may believe they need to intervene thus reducing physical activity levels (Brussoni et al, 2015;Nilsen et al, 2023). This evidence speaks to the need for a shift in educator Cheung et al, 2022;Mak et al, 2021;Tonge et al, 2016). In addition, research may look at the dynamics of how these behaviours are supported or encouraged through the interplay of government policy, centre support and manager knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required in this area to understand the content of games and activities to promote PA in early years settings. This research can then be used to develop effective professional development opportunities for educators, which is an important element of building knowledge and confidence in educators to encourage PA (W. C. Cheung et al, 2022; Mak et al, 2021; Tonge et al, 2016). In addition, research may look at the dynamics of how these behaviours are supported or encouraged through the interplay of government policy, centre support and manager knowledge.…”
Section: Discussionmentioning
confidence: 99%